If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (15a + 12b) + -1(2a + -3b) = 0 Remove parenthesis around (15a + 12b) 15a + 12b + -1(2a + -3b) = 0 15a + 12b + (2a * -1 + -3b * -1) = 0 15a + 12b + (-2a + 3b) = 0 Reorder the terms: 15a + -2a + 12b + 3b = 0 Combine like terms: 15a + -2a = 13a 13a + 12b + 3b = 0 Combine like terms: 12b + 3b = 15b 13a + 15b = 0 Solving 13a + 15b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-15b' to each side of the equation. 13a + 15b + -15b = 0 + -15b Combine like terms: 15b + -15b = 0 13a + 0 = 0 + -15b 13a = 0 + -15b Remove the zero: 13a = -15b Divide each side by '13'. a = -1.153846154b Simplifying a = -1.153846154b
| (u^3)+2u=12 | | 6e-5=7e+6 | | 4ln(x)+5= | | 4x-2+2*4x-1=9 | | 10xy-5xy= | | (3x+5)(4x-9)=0 | | 28x+.13=.17x | | log(x-2)+log(x+2)=1 | | 8t+3=9t-7 | | 8t+3=9+-7 | | 3020=28y+13x | | Lgx=20 | | 50x+50y=50 | | 50x+50y=50 | | 25x+50y=50 | | f(x)=2x^4-3x^3+2x^2-3 | | 8x^2y/12xy | | 7=X+Y*3 | | 7=(7+-3Y)+3Y | | 7=X+3Y | | x+0.25x=150 | | (X+12)*x=5440 | | N=X+Y*3 | | 52p-32=p+3946 | | 49t+64=-3t+792 | | 6n^2+1=0 | | 5n+65=2n+206 | | -94+12y+6=6(3y-5)-4 | | 7x+38=10whatisx | | 1900=0.25x-0.20y | | 5m/14-7m/20 | | 5x-42=168 |